2009
DOI: 10.1186/2047-783x-14-10-426
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of circulating tumour cells in breast cancer patients

Abstract: Background The diagnostic tools to predict the prognosis in patients suffering from breast cancer (BC) need further improvements. New technological achievements like the gene profiling of circulating tumour cells (CTC) could help identify new prognostic markers in the clinical setting. Furthermore, gene expression patterns of CTC might provide important informations on the mechanisms of tumour cell metastasation. Materials and methods We performed realtime-PCR and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Haematological CTC are a prerequisite to distant organ metastasis in many cancer entities [ 7 , 32 - 34 ]. Several studies suggest that only a minority of tumor cells have the ability to invade and metastasize [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haematological CTC are a prerequisite to distant organ metastasis in many cancer entities [ 7 , 32 - 34 ]. Several studies suggest that only a minority of tumor cells have the ability to invade and metastasize [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells entering the circulation depend on the organ microenvironment in order to be able to colonize tissues and to proliferate [ 2 - 6 ]. One of the promising markers for a current risk classification system is the presence of circulating tumor cells (CTC) in the blood of tumor patients [ 7 ]. Braun et al [ 8 ] showed that the presence of micrometastasis in the bone marrow at the time of diagnosis of BC is an independent predictor of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Circulating tumor cells from breast cancer patients were also found to express PDEF. 13,33 Based on the oncogenic properties of PDEF, these findings support a continuing role for PDEF in breast cancer progression.…”
Section: Pdef An Oncogenic Driver Of Breast Cancermentioning
confidence: 77%
“…Δπίζεο ην PBGD δελ έρεη βξεζεί λα έρεη ςεπδνγνλίδηα, κεηώλνληαο θαηά πνιύ ηνπο απαηηνύκελνπο πεηξακαηηθνύο ρεηξηζκνύο[289]. Ωζηόζν, ε έθθξαζε πνιιαπιώλ γνληδίσλ ζε ζρέζε κε ηελ έθθξαζε ελόο γνληδίνπ έρεη ην πιενλέθηεκα αύμεζεο ηεο επαηζζεζίαο αλίρλεπζεο ησλ CTCs θαη παξέρεη ζεκαληηθή πιεξνθνξία ζρεηηθά κε ηελ εηεξνγέλεηα ησλ CTCs[295]. Γηα πξώηε θνξά αλαπηύζζεηαη κεζνδνινγία ηεηξαπιήο πνζνηηθήο PCR γηα ηα γνλίδηα CK-19, HER-2, MAGE-A3 θαη PBGD.…”
unclassified